PELATIHAN K3 MADYA DENGAN STUDI KASUS LINGKUNGAN KERJA PADA PT ALL LIFTING INDONESIA KOTA BATAM - Yunesman; Refdilzon Yasra (Jurnal Pengabdian Ibnu Sina, 2026)
High-risk work environments require a robust safety system and training tailored to on-site conditions. At PT AllLifting Indonesia in Batam, various workplace hazards were identified as insufficiently managed, including theabsence of designated pedestrian pathways, exposed electrical cables, and the use of unprotected equipment. Thisstudy aims to enhance workers’ understanding and skills in identifying and managing occupational risks througha contextualized intermediate-level occupational safety and health (OSH) training program based on real casestudies. The method employed was a community service-based participatory approach involving directobservation, structured interviews, and on-site training activities. Risk identification was conducted usingHIRADC and Job Safety Analysis (JSA) instruments. The results revealed a significant improvement inparticipant comprehension, with the average pre-test score rising from 56% to 84% in the post-test. Participantsalso demonstrated the ability to propose relevant risk control measures based on actual field conditions. Trainingwas delivered through a combination of demonstrations, group discussions, and hands-on exercises using hazardidentification tools at the worksite. Beyond improving knowledge, the program cultivated collective awareness ofthe importance of implementing proper safety procedures. The company responded positively and expressedcommitment to integrating the training recommendations into internal policies. The findings suggest that OSHtraining rooted in real-world data and field-based cases is more effective in fostering safety awareness thanconventional theoretical approaches, and may serve as a replicable training model for similar industrial sectors.